30 Novel Technique of Gastrojejunostomy Tube Insertion to Control Retracted Proximal Stoma. (4th May 2021) - Allen, N; McBride, R; Lindsay, R; Wallace, W
Abstract: Introduction: Extensive small bowel resection for ischaemia can require formation of a proximal jejunostomy. Depending on length of remaining jejunum, a major potential complication is stoma retraction with resultant peritonitis, intra-abdominal sepsis and enterocutaneous fistula formation. We describe a case using a novel technique of inserting a retrograde gastrojejunostomy tube to gain control of an acutely retracted stoma in a 61-year-old patient who developed an enterocutaneous fistula shortly after major resection due to ischaemia. Method: Under fluoroscopic guidance, the retracted proximal limb of the jejunostomy was cannulated antegradely by guide wire. A gastro-jejunostomy tube was inserted retrograde over the guide wire and the tip placed within the stomach. The proximal tube fenestrations were sited within the duodenum and the balloon was inflated to limit enteric content spilling into the peritoneal cavity. Conclusions: This technique enabled drainage of gastroduodenal fluid, minimised spillage into the peritoneal cavity, reduced fistula output and controlled sepsis. This allowed time for nutritional optimisation, better glycaemic control, and endovascular revascularisation in preparation for restoration of intestinal continuity at an appropriate time. This method offered a useful alternative to surgery, in a patient for whom emergency re-exploration of the abdomen would carry significant risk of morbidity or mortality.